Deformation imaging describes right ventricular function better than longitudinal displacement of the tricuspid ring. Issue 4 (30th August 2009) - Giusca, S; Dambrauskaite, V; Scheurwegs, C; D'hooge, J; Claus, P; Herbots, L; Magro, M; Rademakers, F; Meyns, B; Delcroix, M; Voigt, J-U
Abstract : Aims: To quantify right ventricular (RV) function in patients with chronic thromboembolic pulmonary hypertension (CTEPH) before and after pulmonary endarterectomy (PEA). Methods: Out of 33 patients, 16 were evaluated clinically and with echocardiography (conventional and myocardial deformation parameters) before PEA (preop) and at 1 week, 1 month, 3 months and 6 months after PEA. RV fractional area change (RVFAC), tricuspid annular plane systolic excursion (TAPSE) as well as mid-apical and basal peak ejection strain (S) and strain rate (SR) of the RV free wall were measured. Left ventricular (LV) apical lateral wall motion was regarded as indicating changes in overall heart rocking motion (RM). Heart catheterisation was performed before, within 1 week and at 6 months after PEA. Results: Clinical and haemodynamic parameters improved significantly after PEA. This correlated with the improvement in RVFAC, S and SR. TAPSE, on the other hand, showed a biphasic response (14.5 (4) mm preop, 8.5 (2.7) mm at 1 week and 11 (1.5) mm at 6 months). Changes in LV apical motion explain this finding. At baseline, TAPSE was enhanced by rocking motion of the heart as a result of the failing RV. Unloading the RV by PEA normalised the rocking motion and TAPSE decreased. Conclusions: RV function of CTEPH patients improves steadily after PEA. Unlike S, SR and RVFAC, this is not reflected by TAPSE because of postoperative changes in overall heart motion. Motion independent deformation parameters (S, SR) appear superior in the accurate description of regional RV function